Výzkum interakce mezi spolužáky: přehled konverzačněanalytických studií - František Tůma; Linda Nepivodová; Nicola Fořtová (Karolinum Press, 2019)
Interaction among peers (e.g. within pairwork or groupwork) represents an under-researched area in Czech educational sciences. Therefore, in this article we introduce conversation analysis, which provides a theoretical and methodological framework for investigating ongoing interaction. A review of research on peer interaction published internationally in 28 conversation-analytic studies that were selected from the Scopus database is then presented. Although the majority of the studies are related to higher education and to foreign language teaching and learning, some studies were conducted at lower levels of education and in other subjects. The studies show how peers plan and solve tasks, how they learn in interaction (including foreign language acquisition and development of interactional competence), how they teach each other and how they use embodied, language or material resources. It follows that interaction is typically non-linear and dynamic in nature. We contrast these foci with some educational and psychological perspectives on learning and teaching and then discuss the relationship between conversation analysis and educational research.